2020
DOI: 10.3389/fgene.2020.00799
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping, Candidate Gene Identification and Co-segregating Marker Development for the Phytophthora Root Rot Resistance Gene RpsYD25

Abstract: Phytophthora root rot (PRR) caused by Phytophthora sojae is a serious disease of soybean. The most effective disease-control strategy is to deploy resistant cultivars carrying Rps genes. Soybean cultivar Yudou25 can effectively resist pathotypes of P. sojae in China. Previous studies have mapped the Rps gene in Yudou25, RpsYD25, on chromosome 3. In this study, at first RpsYD25 was located between SSR markers Satt1k3 (2.2 cM) and BARCSOYSSR_03_0253 (4.5 cM) by using an F 2:3 population containing 165 families d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Sahoo et al (2017) also reported several NBS-LRR-like genes in genetic investigations of Rps12. Jiang et al (2020) and Zhong et al (2020) also reported NBS-LRR and zinc ion-binding genes as candidate genes by fine mapping of RpsYD25 and RpsGZ.…”
Section: Candidate Genes For Phytophthora Root and Stem Rot Resistancementioning
confidence: 94%
See 1 more Smart Citation
“…Sahoo et al (2017) also reported several NBS-LRR-like genes in genetic investigations of Rps12. Jiang et al (2020) and Zhong et al (2020) also reported NBS-LRR and zinc ion-binding genes as candidate genes by fine mapping of RpsYD25 and RpsGZ.…”
Section: Candidate Genes For Phytophthora Root and Stem Rot Resistancementioning
confidence: 94%
“… Zhong et al (2019) identified RpsX in soybean cultivar Xiu94-11; subsequently, it was revealed that RpsX was located in the 242-kb genomic region spanning the RpsQ locus on chromosome 3. Zhong et al (2020) fine-mapped RpsYD25 in 1127 F 3:4 families derived from “Zaoshu18” and “Yudou25;” subsequently, 7 out of 178 soybean genotypes containing RpsYD25 were identified using five co-segregated SSR markers. Recently, Jiang et al (2020) have fine-mapped RpsGZ to a 367.371-kb genomic region on chromosome 3 in recombinant inbred lines (RILs) derived from a cross of the resistant cultivar “Guizao1” and the susceptible cultivar “BRSMG68.” Sahoo et al (2017) identified Rps12 on chromosome 18 in an RIL population developed by crossing the P .…”
Section: Genetics Of Complete Resistance Versus Partial Resistancementioning
confidence: 99%
“…Controlled by a single gene, it is also easier to select phenotypes during breeding and facilitates their introgression into elite cultivars. Soybean is indeed a rich source of race‐specific resistance as nearly 30 Rps genes have been identified and mapped to nine chromosomes since the 1950s (Zhong et al, 2020). From this catalogue of genes, six have been successfully introgressed into commercial soybean varieties, namely Rps1a , Rps1b , Rps1c , Rps1k , Rps3a , and Rps6 (Abeysekara et al, 2016; Sugimoto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A novel Phytophthora resistance gene, RpsZS18 , was detected on chromosome 2 of the soybean cultivar Zaoshu18 [ 17 ]. RpsYD25 was predicted as a candidate gene and validated to be a diagnostic marker for P. sojae resistance breeding [ 18 ].…”
Section: Introductionmentioning
confidence: 99%